Detecção do Fungo Batrachochytrium dendrobatidis em Anuros no estado do Ceará, Brasil - Mendes, Mirian dos Santos (2021)
Amphibians have the highest species extinction rates when compared to any other vertebrate group. Chytridiomycosis, a disease caused by the fungus Batrachochytrium dendrobatidis (Bd) that has globally affected amphibians since the 1970s, has been considered the main cause of this decline. Taking into account that Brazil is the country with the greatest wealth of amphibians, with many endemic species, it is necessary to understand the effects of chytridiomycosis in Brazilian territory. Adding to this, there are few studies in the semi-arid region of the country. Thus, this study aimed to investigate whether anuran populations residing in the state of Ceará present positive results for the Bd fungus. Pacatuba, Ibiapaba Plateau, Serra de Maranguape, Chapada do Araripe, Farias Brito and Campos Sales. The collection of samples from the skin of amphibians was performed using a swab after capturing the adult frogs. Then, total DNA extraction from the swabs was performed using the PrepMan Kit and the samples were submitted to the PCR technique using specific primers for Bd (Bd1a 5'-CAGTGTGCCATATGTCACG-3' and Bd2a 5'-CATGGTTCATATCTGTCCAG -3'). 125 samples were analyzed, comprising 28 species belonging to 8 anuran families, with 20 (69%) of these species showing positive results for the presence of the Bd fungus. (88%) and Maranguape the place with the lowest proportion of positive species (7%). The present study resulted in the first record of Bd infection for the species Boana raniceps, Dendropsophus nanus, Dendropsophus soaresi, Scinax x-signatus, Leptodactylus troglodytes, Leptodactylus vastus, Physalaemus cicada, Pseudopaludicola mystacalismera, Procertaikismera julysmera and Adenophrys. Worryingly, among the species that showed positive results, there are Pristimantis sp. and Proceratophrys ararype, which have a restricted distribution to high-altitude swamps, forest refuges that are under strong threat from anthropic actions. Therefore, the results of the present study confirm the presence of the Bd fungus in 20 species of anurans and in 6 locations in the state of Ceará, both in Caatinga and swamp areas, and provide the first data to support preventive measures against the Bd fungus in the state of Ceará.